Turkey in the European Union – Dialogue or Collision of Civilizations? (Economic and Political Thought, 2011)
The article is aimed at systematizing the discussion about the Turkishmembership of the European Union. The author presents the difficult historicalTurkish route to the European Union which started in the 1950s whenthe Turkish state joined the North Atlantic Treaty Organization and finishedwith the accession negotiations initiated in 2005.The subject-matter of the analysis is also an answer to the question aboutthe European roots of Turkey. The author discusses the location of Turkeybecause the literature of the topic does not explicitly define whether Turkeyis in Europe or not. He also wonders whether the absence of Christianity asa major religion in Turkey is an obstacle in the process of European integrationand how the Europeans will react to a larger emigration of the Muslimpopulation.As far as the issue of Turkish membership of the European Union isconcerned, the key problems are the effects of such accession. The authorproposes a thesis that Turkish accession to the European Union will basicallystrengthen the position of big countries in the voting procedure of theCouncil of the European Union. However, on the other hand, Turkey will bea big burden for the European budget because it needs many reforms.The article also deals with the issue of substituting the full membershipwith an idea of privileged membership which Turkey is not going to accept,and the Polish involvement in the process of Turkish accession. A discussionabout Turkish accession will continue for many years. Member states’ attitudestowards Ankara’s membership of the European Union differ so muchthat they may be a barrier impossible to overcome.